Metabotropic Glutamate2 Receptors Play a Key Role in Modulating Head Twitches Induced by a Serotonergic Hallucinogen in Mice - Benvenga, Mark J.; Chaney, Stephen F.; Baez, Melvyn; Britton, Thomas C.; Hornback, William J.; Monn, James A.; Marek, Gerard J. (Frontiers in Pharmacology, 2018)
There is substantial evidence that glutamate can modulate the effects of 5-hydroxytryptamine2A (5-HT2A) receptor activation through stimulation of metabotropic glutamate 2/3 (mGlu2/3) receptors in the prefrontal cortex. Here we show that constitutive deletion of the mGlu2 gene profoundly attenuates an effect of 5-HT2A receptor activation using the mouse head twitch response (HTR). MGlu2 and mGlu3 receptor knockout (KO) as well as age-matched ICR (CD-1) wild type (WT) mice were administered (±)1-(2,5-dimethoxy-4-iodophenyl)-2-aminopropane (DOI) and observed for head twitch activity. DOI failed to produce significant head twitches in mGlu2 receptor KO mice at a dose 10-fold higher than the peak effective dose in WT or mGlu3 receptor KO mice. In addition, the mGlu2/3 receptor agonist LY379268, and the mGlu2 receptor positive allosteric modulator (PAM) CBiPES, potently blocked the HTR to DOI in WT and mGlu3 receptor KO mice. Conversely, the mGlu2/3 receptor antagonist LY341495 (10 mg/kg) increased the HTR produced by DOI (3 mg/kg) in mGlu3 receptor KO mice. Finally, the mGlu2 receptor potentiator CBiPES was able to attenuate the increase in the HTR produced by LY341495 in mGlu3 receptor KO mice. Taken together, all of these results are consistent with the hypothesis that that DOI-induced head twitches are modulated by mGlu2 receptor activation. These results also are in keeping with a critical autoreceptor function for mGlu2 receptors in the prefrontal cortex with differential effects of acute vs chronic perturbation (e.g., constitutive mGlu2 receptor KO mice). The robust attenuation of DOI-induced head twitches in the mGlu2 receptor KO mice appears to reflect the critical role of glutamate in ongoing regulation of 5-HT2A receptors in the prefrontal cortex. Future experiments with inducible knockouts for the mGlu2 receptor and/or selective mGlu3 receptor agonists/PAMs/antagonists could provide an important tools in understanding glutamatergic modulation of prefrontal cortical 5-HT2A receptor function.